Management and outcome of patients with chronic myeloid leukemia in blast phase in the tyrosine kinase inhibitor era - analysis of the European LeukemiaNet Blast Phase Registry - Brioli, Annamaria; Lomaia, Elza; Fabisch, Christian; Sacha, Tomasz; Klamova, Hana; Morozova, Elena; Golos, Aleksandra; Ernst, Philipp; Olsson-Stromberg, Ulla; Zackova, Daniela; Nicolini, Franck E.; Bao, Han; et al. (Leukemia, 2024)
Blast phase (BP) of chronic myeloid leukemia (CML) still represents an unmet clinical need with a dismal prognosis. Due to the rarity of the condition and the heterogeneity of the biology and clinical presentation, prospective trials and concise treatment recommendations are lacking. Here we present the analysis of the European LeukemiaNet Blast Phase Registry, an international collection of the clinical presentation, treatment and outcome of blast phases which had been diagnosed in CML patients after 2015. Data reveal the expected heterogeneity of the entity, lacking a clear treatment standard. Outcomes remain dismal, with a median overall survival of 23.8 months (median follow up 27.8 months). Allogeneic stem cell transplantation (alloSCT) increases the rate of deep molecular responses. De novo BP and BP evolving from a previous CML do show slightly different features, suggesting a different biology between the two entities. Data show that outside clinical trials and in a real-world setting treatment of blast phase is individualized according to disease- and patient-related characteristics, with the aim of blast clearance prior to allogeneic stem cell transplantation. AlloSCT should be offered to all patients eligible for this procedure.